THE POETICS OF FRAGILITY: AGEING AND CONTINUITY IN SEAMUS HEANEY’S HUMAN CHAIN - Sameer, Ridha; Singh, Gulab (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study delves into Seamus Heaney’s poetic treatment of ageing, trauma, and continuity within his final collection, Human Chain. Through close analysis of key poems, particularly “Route 110” and “Miracle”, the research highlights how Heaney’s brush with mortality following a stroke informs his reflections on fragility, resilience, and the passage of time. Employing mythological allusions, sensory imagery, and moments of vivid memory, Heaney transforms personal vulnerability into a broader meditation on human existence. “Route 110” explores life’s cyclical nature by retracing formative experiences, while “Miracle” reflects on acts of care and the communal aspects of survival. Together, these poems illustrate Heaney’s ability to intertwine intimate recollections with collective cultural memory, creating a poetics that bridges past and present. This study argues that Heaney’s portrayal of fragility becomes an assertion of continuity and artistic legacy, positioning Human Chain as a testament to the endurance of memory, art, and the human spirit.